Students' Attitude and Motivation towards Arabic Language - Rizki Parahita Anandi (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
This survey research was carried out to determine the students’ level of attitude and motivation towards Arabic language learning, as well as to determine the difference in their attitude and motivation based in their demography. Approximately 288 students of IAIN Salatiga have participated in this survey. A questionnaire was administered to the students to collect the data from the. The questionnaire is four-point likert scale that consist of 21 items. The data was then analyzed using Winstep from Rasch Model and IBS SPSS. The result showed that most students (65%) have moderate level of motivation and attitude towards Arabic language learning. The female students have higher motivation as compared to the male students; therefore, teachers should encourage the male students and help them in the Arabic courses.